Comparing Two Naloxone Tapering Methods in Management of Methadone Intoxication; a Quasi-experimental Study - Zarei, Mohammad Javad; Ramezani, Maral; Sahraie, Zahra; Shadnia, Shahin; Erfan Talab Evini, Peyman; Mostafazadeh, Babak; Rahimi, Mitra (Archives of Academic Emergency Medicine, 2023)
Introduction: Even though naloxone is the main treatment for methadone poisoning treatment there are controversies about the proper method of its tapering. This study aimed to compare two methods in this regard. Method: This study was a prospective, single-blind pilot quasi-experimental study on non-addicted adult patients poisoned with methadone. Patients were randomly divided into 2 groups. In one group, after stabilization of respiratory conditions and consciousness, naloxone was tapered using the half-life of methadone and in the other group, naloxone was tapered using the half-life of naloxone. Recurrence of symptoms and changes in venous blood gas parameters were compared between groups as outcome. Results: 52 patients were included (51.92% female). 31 cases entered Group A (tapering based on methadone’s half-life) and 21 cases entered Group B (tapering based on naloxone’s half-life). The two groups were similar regarding mean age (p = 0.575), gender distribution (p = 0.535), the cause of methadone use (p = 0.599), previous medical history (p = 0.529), previous methadone use (p = 0.654), drug use history (p = 0.444), and vital signs on arrival to emergency department (p = 0.054). The cases of re-decreasing consciousness during tapering (52.38% vs. 25.81%; p = 0.049) and after discontinuation of naloxone (72.73% vs. 37.50%; p = 0.050) were higher in the tapering based on naloxone half-life group. The relative risk reduction (RRR) for naloxone half-life group was -1.03 and for methadone half-life group was 0.51. The absolute risk reduction (ARR) was 0.27 (95% confidence interval (CI) = 0.01-0.53) and the number needed to treat (NNT) was 3.7 (95% CI= 1.87- 150.53). There was not any statistically significant difference between groups regarding pH, HCO3, and PCO2 changes during tapering and after naloxone discontinuation (p > 0.05). However, repeated measures analysis of variance (ANOVA), showed that in the tapering based on methadone’s half-life group, the number of changes and stability in the normal range were better (p < 0.001). Conclusion: It seems that, by tapering naloxone based on methadone’s half-life, not only blood acid-base disorders are treated, but they also remain stable after discontinuation and the possibility of symptom recurrence is reduced.